PENGATURAN HUKUM TERHADAP BATAS LANDAS KONTINEN ANTARA INDONESIA DAN MALAYSIA DI GOSONG NIGER - AMBARITA, JOHN PETRUS ADITIA; Diantha, I Made Pasek; Yasa, Made Maharta (Kertha Semaya : Journal Ilmu Hukum; Vol. 01, No. 01, Januari 2013, 2013)
This paper reviewed about regarding determination of Gosong Niger as the ContinentalShelf is reviewed by the National Law and International Law. The research method usedby the author is the Analytical Descriptive research method. This paper is based onnormative legal research. In terms of Regulation National Law will use the NationalLegislation governing the continental shelf of Indonesia, Government Regulation,Regulation of the President and the Presidential Decree. Rules of International Law beingused are covered by the "Agreement Between the Government of the Republic of Indonesiaand the Government of Malaysia About Decision Boundary Line Between SecondContinental Shelf of 1969", regulation of Gosong Niger included. In this provision itsalready clear regarding the determination of the points geographical coordinates boundaryof the continental shelf, but the actual location of those points on the ocean is not yetdetermined by the two countries, especially in the Gosong Niger. Further regulation thatwill be used is the UNCLOS 1982, the continental shelf settings contained in Chapter VIArticle 76 through Article 85. The results of this research are, that the Gosong Niger(Niger Banks) is a form of natural sand dune formations in shallow water with a physicalconstantly wet. Gosong Niger can’t be categorized as dry coral or island and can be abenchmark for determining the starting point.
Keywords: Gosong Niger, Continental Shelf, Agreement and Indonesia-Malaysia.